A Study on Decoupling of Carbon Emissions from Beijing-Tianjin-Hebei Transport Industry - Li, Xinyue (IOP conference series. Earth and environmental science, 2020)
As the world's largest carbon emitter, the Chinese government is actively taking responsibility for reducing emissions and formulating relevant policies to achieve a low-carbon economy. The transportation industry is the third largest greenhouse gas emission source after the power industry and the steel industry in China, so the transportation industry is an important sector of carbon emission reduction in China. The Beijing-Tianjin-Hebei region is one of the supporting platforms for China's strong competitiveness in the international economic system, but its transportation system develop pment is not balanced, and there are also great differences in energy consumption and carbon emissions. Therefore, it is of great significance to study the correlation between carbon emission and economic growth in The Beijing-Tianjin-Hebei region. In this context, this paper takes the Beijing-Tianjin-Hebei transportation industry as the research center, explores the decoupling relationship between its industry growth and carbon emissions, and gives relevant conclusions.